Study of Melting Temperature of Metals: Pressure Dependence - Hung, Vu Van; Tich, Hoang Van; Hai, Dang Thanh (Communications in Physics, 2011)
The melting temperature of metals are studied using the statistical moment method, going the quasi-harmonic appromations. The melting temperature of metals are calculated as a function of the pressure. We discuss the pressure dependence of melting temperatures of Ce, Fe metals and compare the present results with those of the experimental results